Preparation method of composite coated glass and solar cell
Patent Information
- Application Number
- CN202311832949.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2043-12-27
AI Technical Summary
[0004]本申请的目的在于提供一种复合镀膜玻璃的制备方法和太阳能电池,旨在解决现有的TCO镀膜玻璃存在高温稳定性较差,从而影响太阳能电池的光电转换效率的问题
本申请第一方面提供的复合镀膜玻璃的制备方法,首先在玻璃基底的表面制备屏蔽层,然后在屏蔽层背离玻璃基底的表面制备第一减反射层,接着在第一减反射层背离屏蔽层的表面制备第二减反射层,再在第二减反射层背离第一减反射层的表面制备第一导电层,包括以第一锡源、掺杂剂、催化剂和氧化剂为气体原料进行第一化学气相沉积,最后在第一导电层背离第二减反射层的表面制备第二导电层,包括以第一锡源、掺杂剂、催化剂和氧化剂为气体原料进行第二化学气相沉积,使制得的复合镀膜玻璃结构可在高温下维持稳定。并且使第一化学气相沉积的衬底温度高于第二化学气相沉积的衬底温度,且第一化学气相沉积的衬底温度为660℃以上,以形成结晶度更高和结晶颗粒堆积更紧密、连续性更好且致密度更高的复合透明导电氧化物层,其在高温下不产生明显变化,维持微观结构的稳定性,在高温下的自由载流子的平均自由程远小于晶粒尺寸,可以降低晶界散射对复合透明导电氧化物层的霍尔迁移率的影响,高温下维持良好导电性能,从而赋予复合透明导电氧化物层耐高温特点。此外,本申请制备方法工艺简单,适用于工业化大规模生产和应用。
Smart Images

Figure CN117756415B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of coated glass technology, and particularly relates to a method for preparing composite coated glass and a solar cell. Background Technology
[0002] Transparent conductive oxide (TCO) coated glass serves as the front electrode of thin-film solar cells, acting as both a support material and a window material. It is primarily used in cadmium telluride (CdTe) thin-film solar cells. Functionally, TCO coated glass provides physical and mechanical support for the multilayer film structure of the cell; it allows sunlight to pass through and be absorbed by photovoltaic materials, converting it into electrical energy; and it acts as an electrode material, forming a fundamental building block of photovoltaic devices. Currently, CdTe thin films are mainly prepared using the near-space sublimation method, which requires a substrate temperature (TCO coated glass) of over 600°C to produce high-performance CdTe films. However, with existing technologies, the carrier concentration and mobility of the conductive layer in TCO coated glass change significantly at around 500°C, resulting in poor high-temperature stability and consequently affecting the photoelectric conversion efficiency of CdTe thin-film solar cells.
[0003] Therefore, it is necessary to develop a method for preparing composite coated glass in order to produce composite coated glass with good high-temperature stability. Summary of the Invention
[0004] The purpose of this application is to provide a method for preparing composite coated glass and a solar cell, aiming to solve the problem that existing TCO coated glass has poor high-temperature stability, which affects the photoelectric conversion efficiency of solar cells.
[0005] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows: In a first aspect, this application provides a method for preparing composite coated glass, comprising the following steps: Provide glass substrate; A shielding layer is prepared on the surface of a glass substrate; A first antireflective layer is prepared on the surface of the shielding layer that is away from the glass substrate; A second antireflection layer is prepared on the surface of the first antireflection layer that is away from the shielding layer; A first conductive layer is prepared on the surface of the second antireflection layer away from the first antireflection layer, including a first chemical vapor deposition using a first tin source, dopant, catalyst and oxidant as gaseous raw materials; A second conductive layer is prepared on the surface of the first conductive layer away from the second antireflection layer, including a second chemical vapor deposition using a first tin source, dopant, catalyst and oxidant as gaseous raw materials to obtain a composite coated glass; In this process, the substrate temperature of the first chemical vapor deposition is higher than that of the second chemical vapor deposition, and the substrate temperature of the first chemical vapor deposition is above 660°C, so as to form a high-temperature resistant composite transparent conductive oxide layer.
[0006] In this embodiment, the substrate temperature for the first chemical vapor deposition is above 670°C.
[0007] In this embodiment, the substrate temperature for the second chemical vapor deposition is above 650°C.
[0008] In the embodiments, the first tin source is selected from at least one of trichloromonobutyltin, dichlorodimethyltin, tetramethyltin, and tin tetrachloride; the dopant is selected from at least one of ammonium fluoride, trifluoroacetic acid, hydrofluoric acid, and tetrabutylammonium fluoride; the catalyst is selected from deionized water; and the oxidant is selected from oxygen.
[0009] In the embodiments, the molar ratio of the first tin source, dopant, catalyst and oxidant is 1:(0.41~1.16):(3.16~5.82):(8.19~13.45).
[0010] In an embodiment, the step of preparing a first antireflection layer on the surface of the shielding layer away from the glass substrate includes: using nitrogen and helium as carrier gases, and silane, ethylene and oxygen in a molar ratio of 1:(5.3~6.7):(3.2~4.8) as gaseous raw materials, and performing a third chemical vapor deposition on the surface of the shielding layer away from the glass substrate at a substrate temperature above 680°C to obtain the first antireflection layer.
[0011] In an embodiment, the step of preparing a second antireflection layer on the surface of the first antireflection layer away from the shielding layer includes: using nitrogen and helium as carrier gases, and silane, ethylene and oxygen in a molar ratio of 1:(5.3~6.7):(3.2~4.8) as gas raw materials, performing a fourth chemical vapor deposition on the surface of the shielding layer away from the glass substrate at a substrate temperature above 670°C to obtain the second antireflection layer.
[0012] In an embodiment, the step of preparing a shielding layer on the surface of a glass substrate includes: using nitrogen and helium as carrier gases, and using isopropyl titanate and oxygen in a molar ratio of 1:(3.4~7.1) as gas raw materials, performing a fifth chemical vapor deposition on the surface of a glass substrate at a temperature above 690°C to obtain a shielding layer.
[0013] In the embodiments, the step of preparing a shielding layer on the surface of a glass substrate includes: using nitrogen and helium as carrier gases, and a first tin source, tetraethyl orthosilicate, triethyl phosphite, deionized water, and oxygen in a molar ratio of 1:(0.96~1.32):(0.48~0.72):(0.94~1.29):(19.67~22.09) as gas raw materials, performing a fifth chemical vapor deposition on the surface of a glass substrate at a temperature above 690°C to obtain a shielding layer.
[0014] In the embodiments, the shielding layer includes a tin dioxide layer, a titanium dioxide layer, and a SnSiO layer. x Any of the P-layers, the refractive index of the shielding layer is 1.63~2.8, and the thickness of the shielding layer is 40nm~70nm.
[0015] In the embodiment, the first antireflection layer and the second antireflection layer are silicon dioxide layers, the refractive index of the first antireflection layer is 1.45~1.52, the refractive index of the second antireflection layer is 1.42~1.5, and the thickness of the first antireflection layer and the second antireflection layer is 10nm~30nm.
[0016] In the embodiment, the first conductive layer is a fluorine-doped tin dioxide layer, the refractive index of the first conductive layer is 1.82~1.9, and the thickness of the first conductive layer is 150nm~400nm.
[0017] In this embodiment, the second conductive layer is a fluorine-doped tin dioxide layer, the refractive index of the second conductive layer is 1.79~1.86, and the thickness of the second conductive layer is 200nm~400nm.
[0018] In the embodiments, the transmittance of the composite coated glass is 81%~85%.
[0019] In this embodiment, the carrier concentration of the composite coated glass is 2.6 × 10⁻⁶. 20 ~4.2×10 20 / cm - ³.
[0020] In the embodiments, the resistance of the composite coated glass is 6~12Ω / □.
[0021] In the embodiment, after the composite coated glass passes the high-temperature heat resistance test, the carrier concentration change rate of the composite coated glass is less than 5%; wherein, the high-temperature heat resistance test is set to the composite coated glass being kept in an air atmosphere at a temperature of 600-700℃ for at least 2.5 hours.
[0022] Secondly, this application provides a solar cell, including a composite coated glass prepared by the preparation method provided in this application.
[0023] Compared with the prior art, this application has the following beneficial effects: The method for preparing composite coated glass provided in the first aspect of this application firstly prepares a shielding layer on the surface of a glass substrate, then prepares a first antireflection layer on the surface of the shielding layer away from the glass substrate, then prepares a second antireflection layer on the surface of the first antireflection layer away from the shielding layer, then prepares a first conductive layer on the surface of the second antireflection layer away from the first antireflection layer, including performing a first chemical vapor deposition using a first tin source, dopant, catalyst, and oxidant as gaseous raw materials, and finally prepares a second conductive layer on the surface of the first conductive layer away from the second antireflection layer, including performing a second chemical vapor deposition using a first tin source, dopant, catalyst, and oxidant as gaseous raw materials, so that the resulting composite coated glass structure can remain stable at high temperatures. Furthermore, the substrate temperature for the first chemical vapor deposition is higher than that for the second chemical vapor deposition, with the first chemical vapor deposition temperature exceeding 660°C. This results in a composite transparent conductive oxide layer with higher crystallinity, denser grain packing, better continuity, and higher density. This layer does not undergo significant changes at high temperatures, maintaining the stability of its microstructure. At high temperatures, the mean free path of free carriers is much smaller than the grain size, reducing the impact of grain boundary scattering on the Hall mobility of the composite transparent conductive oxide layer and maintaining good conductivity at high temperatures, thus endowing the composite transparent conductive oxide layer with high-temperature resistance. In addition, the preparation method of this application is simple and suitable for large-scale industrial production and application.
[0024] The solar cell provided in the second aspect of this application has a high photoelectric conversion efficiency because it contains composite coated glass prepared by the preparation method provided in this application. Attached Figure Description
[0025] To more clearly illustrate the technical solutions in the embodiments of this application, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 This is a process flow diagram of the method for preparing composite coated glass provided in the embodiments of this application; Figure 2 This is a schematic diagram of the structure of a composite coated glass provided in an embodiment of this application; Figure 3 These are XRD patterns of the composite coated glass provided in Embodiment 1 and Comparative Example 1 of this application before and after high-temperature heat treatment; Figure 4 This is a SEM image of the composite coated glass provided in Embodiment 1 of this application; Figure 5This is a SEM image of the composite coated glass provided in Embodiment 1 of this application after high-temperature heat treatment; Figure 6 These are the transmittance and reflectance curves of the composite coated glass provided in Example 1 and Comparative Example 1 of this application before and after high-temperature heat treatment; The following are the labeling elements in the figure: 1—Glass substrate, 2—Shielding layer, 3—First antireflection layer, 4—Second antireflection layer, 5—First conductive layer, 6—Second conductive layer. Detailed Implementation
[0027] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0028] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0029] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0030] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0031] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.
[0032] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a well-known unit of mass in the chemical industry, such as µg, mg, g, or kg.
[0033] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.
[0034] The first aspect of this application provides a method for preparing composite coated glass, such as... Figure 1 As shown, it includes the following steps: S01: Provides a glass substrate; S02: Prepare a shielding layer on the surface of a glass substrate; S03: Prepare the first anti-reflection layer on the surface of the shielding layer that is away from the glass substrate; S04: Prepare a second antireflection layer on the surface of the first antireflection layer that is away from the shielding layer; S05: A first conductive layer is prepared on the surface of the second antireflection layer away from the first antireflection layer, including a first chemical vapor deposition using a first tin source, dopant, catalyst and oxidant as gaseous raw materials; S06: A second conductive layer is prepared on the surface of the first conductive layer away from the second antireflection layer, including a second chemical vapor deposition using a first tin source, dopant, catalyst and oxidant as gas raw materials to obtain a composite coated glass; In this process, the substrate temperature of the first chemical vapor deposition is higher than that of the second chemical vapor deposition, and the temperature of the first chemical vapor deposition is above 660°C, so as to form a high-temperature resistant composite transparent conductive oxide layer.
[0035] The method for preparing composite coated glass provided in this application embodiment first prepares a shielding layer on the surface of a glass substrate, then prepares a first antireflection layer on the surface of the shielding layer away from the glass substrate, then prepares a second antireflection layer on the surface of the first antireflection layer away from the shielding layer, then prepares a first conductive layer on the surface of the second antireflection layer away from the first antireflection layer, including performing a first chemical vapor deposition using a first tin source, dopant, catalyst, and oxidant as gaseous raw materials, and finally prepares a second conductive layer on the surface of the first conductive layer away from the second antireflection layer, including performing a second chemical vapor deposition using a first tin source, dopant, catalyst, and oxidant as gaseous raw materials, so that the prepared composite coated glass structure can remain stable at high temperatures. Furthermore, the substrate temperature for the first chemical vapor deposition is higher than that for the second chemical vapor deposition, with the first chemical vapor deposition temperature exceeding 660°C. This results in a composite transparent conductive oxide layer with higher crystallinity, denser grain packing, better continuity, and higher density. This layer does not undergo significant changes at high temperatures, maintaining the stability of its microstructure. At high temperatures, the mean free path of free carriers is much smaller than the grain size, reducing the impact of grain boundary scattering on the Hall mobility of the composite transparent conductive oxide layer and maintaining good conductivity at high temperatures, thus endowing the composite transparent conductive oxide layer with high-temperature resistance. In addition, the preparation method of this application is simple and suitable for large-scale industrial production and application.
[0036] In step S01, the glass substrate is a float glass substrate with a transmittance ≥89% and a thickness of 2mm~3.5mm. The float glass substrate can be any one of ordinary float glass, high-white float glass, or ultra-white float glass.
[0037] In step S02, the step of preparing a shielding layer on the surface of the glass substrate includes: using nitrogen and helium as carrier gases, and using isopropyl titanate and oxygen in a molar ratio of 1:(3.4~7.1) as gas raw materials, performing fifth chemical vapor deposition on the surface of the glass substrate at a temperature above 690°C to obtain the shielding layer. In the exemplary example, the molar ratio of isopropyl titanate to oxygen can be typical but not limiting molar ratios such as 1:3.4, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, and 1:7.1. The glass substrate temperature for fifth chemical vapor deposition can further be above 695°C, above 700°C, above 705°C, above 710°C, above 715°C, or above 720°C. In the exemplary example, the glass substrate temperature can be typical but not limiting temperatures such as 690~720°C. This molar ratio and temperature range are conducive to the formation of a more uniform and dense titanium dioxide layer, which can better block the diffusion of Na and K ions from the glass substrate into the conductive layer, thus resulting in a better shielding effect.
[0038] In some specific embodiments, in the float glass tin bath forming area, an online float glass coating equipment is installed above the float glass substrate. Nitrogen and helium are used as carrier gases. Isopropyl titanate and oxygen with a gas raw material molar ratio of 1:(3.4~7.1) are introduced into the tin bath. The float glass substrate is pulled at a pulling speed of 300m / h~660m / h. Chemical vapor deposition is performed on the surface of the float glass substrate at a temperature above 690°C to form a titanium dioxide layer.
[0039] In some embodiments, the step of preparing a shielding layer on the surface of a glass substrate includes: using nitrogen and helium as carrier gases, and a first tin source, tetraethyl orthosilicate, triethyl phosphite, deionized water, and oxygen in a molar ratio of 1:(0.96~1.32):(0.48~0.72):(0.94~1.29):(19.67~22.09) as gaseous raw materials, performing fifth chemical vapor deposition on the surface of a glass substrate at a temperature above 690°C to obtain the shielding layer. In the embodiments, the first tin source may be selected from at least one of trichloromonobutyltin, dichlorodimethyltin, tetramethyltin, and tin tetrachloride. In the example, the molar ratio of the first tin source, tetraethyl orthosilicate, triethyl phosphite, deionized water, and oxygen can be typical but not limiting molar ratios such as 1:0.96:0.48:0.94:19.67, 1:1.32:0.72:1.29:22.09, and 1:1.1:0.6:1.1:21. The glass substrate temperature for the fifth chemical vapor deposition can further be above 695°C, above 700°C, above 705°C, above 710°C, above 715°C, or above 720°C. In the example, the glass substrate temperature can be typical but not limiting temperatures such as 690~720°C. This molar ratio and temperature range are beneficial for forming SnSiO with better uniformity and density. x The P layer can better block the diffusion of Na and K ions from the glass substrate into the conductive layer, thus providing a better shielding effect.
[0040] In some specific embodiments, in the float glass tin bath forming area, an online float glass coating device is installed above the float glass substrate. Nitrogen and helium are used as carrier gases. Trichlorobutyltin, tetraethyl orthosilicate, triethyl phosphite, deionized water, and oxygen are introduced into the tin bath in a gaseous raw material molar ratio of 1:(0.96~1.32):(0.48~0.72):(0.94~1.29):(19.67~22.09). The float glass substrate is pulled at a speed of 300m / h~660m / h, and chemical vapor deposition is performed on the glass substrate surface at a temperature of 690~720℃ to form SnSiO. x :P layer.
[0041] In some embodiments, the shielding layer includes a tin dioxide layer, a titanium dioxide layer, and a SnSiO layer. x Any of the P-layers, the refractive index of the shielding layer is 1.63~2.8, and the thickness of the shielding layer is 40nm~70nm.
[0042] In step S03, the step of preparing the first antireflection layer on the surface of the shielding layer away from the glass substrate includes: using nitrogen and helium as carrier gases, and silane, ethylene, and oxygen in a molar ratio of 1:(5.3~6.7):(3.2~4.8) as gaseous raw materials, performing a third chemical vapor deposition on the surface of the shielding layer away from the glass substrate at a substrate temperature above 680°C to obtain the first antireflection layer. The substrate temperature for the third chemical vapor deposition can further be above 682°C, above 684°C, above 686°C, above 688°C, or above 690°C. In the exemplary example, the substrate temperature for the third chemical vapor deposition can be a typical but not limiting temperature such as 680°C to 690°C.
[0043] In step S04, the step of preparing a second antireflection layer on the surface of the first antireflection layer away from the shielding layer includes: using nitrogen and helium as carrier gases, and silane, ethylene, and oxygen in a molar ratio of 1:(5.3~6.7):(3.2~4.8) as gaseous raw materials, performing a fourth chemical vapor deposition on the surface of the shielding layer away from the glass substrate at a substrate temperature above 670°C to obtain the second antireflection layer. The substrate temperature for the fourth chemical vapor deposition can further be above 672°C, above 674°C, above 676°C, above 678°C, or above 680°C. In the exemplary example, the substrate temperature for the fourth chemical vapor deposition can be a typical but not limiting temperature such as 670°C to 680°C.
[0044] Within the substrate temperature range and the molar ratio range of silane, ethylene and oxygen in the aforementioned third and fourth chemical vapor deposition processes, a refractive index gradient is formed between the first and second antireflection layers. This results in a composite antireflection layer composed of the first and second antireflection layers having low light reflectivity and high transmittance, which is beneficial for achieving higher photoelectric conversion efficiency in the composite coated glass.
[0045] In some specific embodiments, in the float glass tin bath forming area, an online float glass coating equipment is installed above the float glass substrate with a deposited shielding layer. Nitrogen is used as the carrier gas, and silane, ethylene and oxygen in a gas raw material molar ratio of 1:(5.3~6.7):(3.2~4.8) are introduced into the tin bath. The float glass substrate is pulled at a pulling speed of 300m / h~660m / h, and the temperature of the float glass substrate is above 680°C. A third chemical vapor deposition is performed on the surface of the shielding layer on the float glass substrate to form a first silicon dioxide layer.
[0046] In some specific embodiments, in the float glass tin bath forming area, an online float glass coating equipment is installed above the float glass substrate on which a shielding layer and a first antireflective layer have been deposited. Nitrogen is used as the carrier gas, and silane, ethylene and oxygen in a molar ratio of 1:(5.3~6.7):(3.2~4.8) are introduced into the tin bath. The float glass substrate is pulled at a pulling speed of 300m / h~660m / h, and the temperature of the float glass substrate is above 670°C. A fourth chemical vapor deposition is performed on the surface of the first antireflective layer on the float glass substrate away from the shielding layer to form a second silicon dioxide layer.
[0047] In some embodiments, the first antireflection layer and the second antireflection layer are silicon dioxide layers, the refractive index of the first antireflection layer is 1.45~1.52, the refractive index of the second antireflection layer is 1.42~1.5, and the thickness of the first antireflection layer and the second antireflection layer is 10nm~30nm.
[0048] In step S05, the substrate temperature for the first chemical vapor deposition is above 660°C, which can be above 662°C, 664°C, 666°C, or 668°C. In some embodiments, it is further preferred to be above 670°C, 672°C, 674°C, 676°C, 678°C, or 680°C. In exemplary examples, it can be a typical but not limiting temperature such as 670°C to 680°C. Within this temperature range, it is beneficial to form a first transparent conductive oxide layer with higher crystallinity and larger grain size, making the mean free path of free carriers at high temperatures much smaller than the grain size. This reduces the influence of grain boundary scattering on the Hall mobility of the first transparent conductive oxide layer, which is beneficial to improving high-temperature stability, thereby endowing the first conductive layer with high-temperature resistance.
[0049] In step S06, the substrate temperature for the second chemical vapor deposition is above 650°C, which can be above 652°C, 654°C, 656°C, or 658°C. In some embodiments, it is further preferred to be above 660°C, 662°C, 664°C, 666°C, 668°C, or 670°C. In exemplary examples, the substrate temperature for the second chemical vapor deposition can be a typical but not limiting temperature such as 650°C to 670°C. This temperature range is beneficial for forming a second transparent conductive oxide layer with higher crystallinity and larger grain size, making the mean free path of free carriers at high temperatures much smaller than the grain size. This reduces the influence of grain boundary scattering on the Hall mobility of the second transparent conductive oxide layer, which is beneficial for improving high-temperature stability, thereby endowing the second conductive layer with high-temperature resistance.
[0050] In some embodiments, in the first chemical vapor deposition and the second chemical vapor deposition, the molar ratio of the first tin source, dopant, catalyst, and oxidant is 1:(0.41~1.16):(3.16~5.82):(8.19~13.45). In exemplary cases, the ratios can be 1:0.41:3.16:8.19, 1:1.16:5.82:13.45, or 1:0.8:4.5:11. Within this molar ratio range, the resulting composite transparent conductive oxide layer, composed of the first and second transparent conductive oxide layers, not only exhibits good conductivity but also high crystallinity and large grain size. This results in a mean free path of free carriers at high temperatures that is much smaller than the grain size, reducing the influence of grain boundary scattering on the Hall mobility of the composite transparent conductive oxide layer. This is beneficial for improving high-temperature stability, thereby endowing the composite transparent conductive oxide layer with high-temperature resistance.
[0051] In some specific embodiments, in the float glass tin bath forming area, an online float glass coating equipment is installed above the float glass substrate on which a shielding layer, a first antireflective layer, and a second antireflective layer have been deposited. Nitrogen and helium are used as carrier gases. A first tin source, dopant, catalyst, and oxidant with a gas raw material molar ratio of 1:(0.41~1.16):(3.16~5.82):(8.19~13.45) are introduced into the tin bath. The float glass substrate is pulled at a pulling speed of 300m / h~660m / h. The temperature of the float glass substrate is greater than 670°C. A first chemical vapor deposition is performed on the surface of the second antireflective layer on the float glass substrate that is away from the surface of the first antireflective layer to form a first transparent conductive oxide layer (first conductive layer).
[0052] In some specific embodiments, in the float glass tin bath forming area, an online float glass coating device is installed above a float glass substrate on which a shielding layer, a first antireflective layer, a second antireflective layer, and a first conductive layer are deposited. Nitrogen and helium are used as carrier gases. A first tin source, dopant, catalyst, and oxidant with a gas raw material molar ratio of 1:(0.41~1.16):(3.16~5.82):(8.19~13.45) are introduced into the tin bath. The float glass substrate is pulled at a pulling speed of 300m / h~660m / h. The temperature of the float glass substrate is greater than 660°C. A second chemical vapor deposition is performed on the surface of the first conductive layer on the float glass substrate that is away from the second antireflective layer to form a second transparent conductive oxide layer (second conductive layer).
[0053] In some embodiments, the first tin source may be selected from at least one of trichloromonobutyltin, dichlorodimethyltin, tetramethyltin, and tin tetrachloride. In an exemplary embodiment, the first tin source may be selected from one or more mixtures of trichloromonobutyltin, dichlorodimethyltin, tetramethyltin, and tin tetrachloride. The dopant may be selected from at least one of ammonium fluoride, trifluoroacetic acid, hydrofluoric acid, and tetrabutylammonium fluoride. In an exemplary embodiment, the dopant may be selected from one or more mixtures of ammonium fluoride, trifluoroacetic acid, hydrofluoric acid, and tetrabutylammonium fluoride. These first tin sources and dopant can form a first conductive layer of fluorine-doped tin dioxide, forming donor levels and contributing to improved conductivity of the first conductive layer. The catalyst may be selected from deionized water; deionized water, as a catalyst, helps to control the crystallinity and grain size of the formed first conductive layer, thereby contributing to improved high-temperature stability of the first conductive layer. The oxidant may be selected from oxygen.
[0054] In some embodiments, the first conductive layer is a fluorine-doped tin dioxide layer, the refractive index of the first conductive layer is 1.82~1.9, and the thickness of the first conductive layer is 150nm~400nm.
[0055] In some embodiments, the second conductive layer is a fluorine-doped tin dioxide layer, the refractive index of the second conductive layer is 1.79~1.86, and the thickness of the second conductive layer is 200nm~400nm.
[0056] In some embodiments, the substrate temperature of the first chemical vapor deposition is higher than that of the second chemical vapor deposition, forming a high-temperature resistant composite transparent conductive oxide layer. This results in the crystallinity of the first conductive layer of the composite transparent conductive oxide layer being higher than that of the second conductive layer, the grain size of the first conductive layer being larger than that of the second conductive layer, and the refractive index of the second conductive layer being lower than that of the first conductive layer. In this way, the first conductive layer and the second conductive layer directly form a refractive index gradient, which can improve the transmittance of the composite coated glass and thus have a higher photoelectric conversion efficiency.
[0057] In some embodiments, the transmittance of the composite coated glass is 81% to 85%.
[0058] In some embodiments, the carrier concentration of the composite coated glass is 2.6 × 10⁻⁶. 20 ~4.2×10 20 / cm - ³.
[0059] In some embodiments, the resistance of the composite coated glass is 6~12Ω / □.
[0060] In some embodiments, after the composite coated glass passes the high-temperature heat resistance test, the carrier concentration change rate of the composite coated glass is less than 5%. In exemplary cases, the carrier concentration change rate of the composite coated glass after the high-temperature heat resistance test can be less than 4%, less than 3%, less than 2%, less than 1%, or less than 0.5%. The high-temperature heat resistance test is set to maintain the composite coated glass at a temperature of 600-700°C in an air atmosphere for at least 2.5 hours. The carrier concentration change rate is the ratio of the difference in carrier concentration before and after the high-temperature heat resistance test to the carrier concentration before the high-temperature heat resistance test.
[0061] The second aspect of this application provides a solar cell, including a composite coated glass prepared by the preparation method provided in this application. This glass has the characteristic of maintaining good and stable photoelectric performance at high temperatures in the preparation and application of solar cells. Therefore, the solar cell of this application has a high photoelectric conversion efficiency.
[0062] The following description is based on specific embodiments.
[0063] Example 1 This embodiment provides a method for preparing composite coated glass.
[0064] The method for preparing this composite coated glass includes the following steps: S1: In the float glass tin bath forming area with a drawing capacity of 520t / d, a coating reactor is installed above the float glass with a thickness of 4mm. S2: Using nitrogen and helium as carrier gases, and with a molar ratio of isopropyl titanate (evaporation temperature 150℃) to oxygen of 1:5, isopropyl titanate and oxygen are introduced into the coating reactor. The flow rates of isopropyl titanate, oxygen, nitrogen and helium are controlled by flow meters to make the total gas volume 600 slpm. A chemical vapor phase reaction is carried out on the surface of a float glass substrate at 690℃ to form a titanium dioxide layer. S3: Using nitrogen as the carrier gas, silane, ethylene and oxygen are introduced into the coating reactor according to the molar ratio of gaseous raw materials silane, ethylene and oxygen of 1:6:4. The flow rates of silane, ethylene, oxygen and nitrogen are controlled by flow meters to make the total gas volume 530 slpm. A chemical vapor phase reaction is carried out on the shielding layer surface on a float glass substrate at 680℃ to form the first silicon dioxide layer. S4: Using nitrogen as the carrier gas, silane, ethylene and oxygen are introduced into the coating reactor according to the molar ratio of gaseous raw materials silane, ethylene and oxygen of 1:6:4. The flow rates of silane, ethylene, oxygen and nitrogen are controlled by flow meters to make the total gas volume 530 slpm. The first silicon dioxide layer on the float glass substrate at 670℃ undergoes a chemical vapor phase reaction on the surface away from the shielding layer to form the second silicon dioxide layer. S5: Using nitrogen and helium as carrier gases, and with the molar ratio of gaseous raw materials monobutyltin trichloride, trifluoroacetic acid, deionized water and oxygen being 1:0.8:4.5:10.5, monobutyltin trichloride, trifluoroacetic acid, deionized water and oxygen are introduced into the coating reactor. The flow rates of monobutyltin trichloride, trifluoroacetic acid, deionized water and oxygen are controlled by flow meters to make the total gas volume 710 slpm. A chemical vapor phase reaction is carried out on the surface of the second silicon dioxide layer on the float glass substrate at 660℃, away from the surface of the first silicon dioxide layer, to form the first fluorine-doped tin dioxide layer. S6: Using nitrogen and helium as carrier gases, and with the molar ratio of gaseous raw materials monobutyltin trichloride, trifluoroacetic acid, deionized water, and oxygen being 1:0.8:4.5:10.5, monobutyltin trichloride, trifluoroacetic acid, deionized water, and oxygen are introduced into the coating reactor. The flow rates of monobutyltin trichloride, trifluoroacetic acid, deionized water, and oxygen are controlled by flow meters to ensure a total gas volume of 710 slpm. A chemical vapor phase reaction is carried out on the surface of the first fluorine-doped tin dioxide layer on a float glass substrate at 650℃, away from the second silicon dioxide layer, to form the second fluorine-doped tin dioxide layer, thus obtaining the composite coated glass.
[0065] The composite coated glass prepared in this embodiment, such as Figure 2 As shown, the structure includes a float glass substrate 1, a shielding layer 2, a first antireflective layer 3, a second antireflective layer 4, a first conductive layer 5, and a second conductive layer 6, which are sequentially stacked. The shielding layer 2 is a titanium dioxide layer with a refractive index of 2.63 and a thickness of 43 nm; the first antireflective layer 3 is a silicon dioxide layer with a refractive index of 1.48 and a thickness of 27 nm; the second antireflective layer 4 is a silicon dioxide layer with a refractive index of 1.46 and a thickness of 30 nm; the first conductive layer 5 is a fluorine-doped tin dioxide layer with a refractive index of 1.9 and a thickness of 230 nm; and the second conductive layer 6 is a fluorine-doped tin dioxide layer with a refractive index of 1.86 and a thickness of 250 nm.
[0066] Example 2 This embodiment provides a method for preparing composite coated glass.
[0067] The difference between the steps of the preparation method of the composite coated glass and those of Example 1 is that in step S5, a chemical vapor phase reaction is carried out on the surface of the second silicon dioxide layer on the float glass substrate at 680°C, away from the surface of the first silicon dioxide layer. In step S6, a chemical vapor phase reaction is carried out on the surface of the first fluorine-doped tin dioxide layer on a float glass substrate at 670°C, away from the second silicon dioxide layer.
[0068] The difference between the composite coated glass prepared in this embodiment and that in embodiment 1 is that the first conductive layer 5 is a fluorine-doped tin dioxide layer with a refractive index of 1.82 and a thickness of 230 nm, and the second conductive layer 6 is a fluorine-doped tin dioxide layer with a refractive index of 1.7 and a thickness of 250 nm.
[0069] Comparative Example 1 This comparative example provides a method for preparing composite coated glass, specifically including the following steps: S1: In the float glass tin bath forming area with a drawing capacity of 520t / d, a coating reactor is installed on the float glass substrate with a thickness of 4mm. S2: Using nitrogen and helium as carrier gases, monobutyltin trichloride (evaporation temperature 180℃), deionized water (evaporation temperature 150℃) and oxygen are introduced into the coating reactor at a molar ratio of 1:1.57:22. The flow rates of monobutyltin trichloride, deionized water, oxygen, nitrogen and helium are controlled by flow meters to make the total gas volume 650 slpm. A chemical vapor phase reaction is carried out on the float glass surface at 680℃ to form a shielding layer. S3: Using nitrogen as the carrier gas, silane, ethylene and oxygen are introduced into the coating reactor according to the molar ratio of gaseous raw materials silane, ethylene and oxygen of 1:6:4. The flow rates of silane, ethylene, oxygen and nitrogen are controlled by flow meters to make the total gas volume 530 slpm. A chemical vapor phase reaction is carried out on the shielding layer surface on a float glass substrate at 660℃ to form an anti-reflection layer. S4: Using nitrogen and helium as carrier gases, and with the molar ratio of gaseous raw materials monobutyltin trichloride, trifluoroacetic acid, deionized water, and oxygen being 1:0.8:4.5:10.5, monobutyltin trichloride, trifluoroacetic acid, deionized water, and oxygen are introduced into the coating reactor. The flow rates of monobutyltin trichloride, trifluoroacetic acid, deionized water, and oxygen are controlled by flow meters to ensure a total gas volume of 710 slpm. A chemical vapor phase reaction is carried out on the antireflection layer on a float glass substrate at 550℃, away from the shielding layer surface, to form the first conductive layer.
[0070] S5: Using nitrogen and helium as carrier gases, and with the molar ratio of gaseous raw materials monobutyltin trichloride, trifluoroacetic acid, deionized water, and oxygen being 1:0.8:4.5:10.5, monobutyltin trichloride, trifluoroacetic acid, deionized water, and oxygen are introduced into the coating reactor. The flow rates of monobutyltin trichloride, trifluoroacetic acid, deionized water, and oxygen are controlled by flow meters to ensure a total gas volume of 710 slpm. A chemical vapor phase reaction is carried out on the antireflection layer of a float glass substrate at 550℃, away from the shielding layer surface, to form a second conductive layer, thus obtaining composite coated glass.
[0071] The composite coated glass prepared in this comparative example includes a float glass substrate, a shielding layer, an antireflective layer, and a conductive layer stacked sequentially. The shielding layer is a tin dioxide layer with a refractive index of 1.89 and a thickness of 27 nm; the antireflective layer is a silicon dioxide layer with a refractive index of 1.49 and a thickness of 44 nm; and the first and second conductive layers are fluorine-doped tin dioxide layers with a refractive index of 1.81 and a thickness of 250 nm.
[0072] Analysis of relevant performance tests before and after high-temperature heat resistance test: (1) The composite coated glass prepared in Example 1 and Comparative Example 1 of this application was placed in an air atmosphere (oxygen content of about 20%), heated to 650°C and kept at a constant temperature for 4 hours, and then XRD tests were performed before and after the high-temperature heat treatment. The test results are as follows. Figure 3 As shown: from Figure 3 It can be seen that the first conductive layer 5 and the second conductive layer 6 of the composite coated glass prepared in Example 1 and Comparative Example 1 of this application are mainly grown along the (110) preferred orientation. Furthermore, the (110) strength of the high-temperature resistant composite coated glass of Example 1 of this application is significantly higher than that of Comparative Example 1, the crystallinity is more than 50%, and the main crystal orientations are (110), (101), (200), and (211). Moreover, the crystallinity and main crystal orientation remain unchanged after high-temperature heat treatment. This indicates that the first conductive layer 5 and the second conductive layer 6 of the composite coated glass prepared in the examples of this application have higher crystallinity and maintain the corresponding crystallinity and main crystal orientation at high temperature.
[0073] (2) The composite coated glass prepared in Example 1 of this application was subjected to field emission scanning electron microscopy (SEM) tests before and after high-temperature heat treatment. The test results are as follows: Figure 4 (Before high-temperature heat treatment) and Figure 5 As shown (after high-temperature heat treatment): from Figure 4 and Figure 5 It can be seen that the composite coated glass prepared in Example 1 of this application has a grain size of more than 50 nm on the surface of the thin film before high temperature heat treatment. The grains are densely packed, have good continuity and high density. The grain outline is sharper and clearer after high temperature heat treatment. Furthermore, the grain size of the conductive layer of the composite coated glass does not change much after high temperature heat treatment, indicating that the composite coated glass prepared in Example 1 of this application has better microstructure stability at high temperature.
[0074] (3) The high-temperature resistant composite coated glass prepared in Example 1 of this application and the composite coated glass prepared in Comparative Example 1 were subjected to optical performance tests before and after high-temperature heat treatment, respectively. The test results are as follows: Figure 6 As shown: from Figure 6It can be seen that the composite coated glass prepared in Comparative Example 1 exhibits reduced absorption of carrier ion concentration by photons in the near-infrared range of 780nm-2500nm before and after heat treatment, leading to an increase in film transmittance. However, the high-temperature resistant composite coated glass prepared in Example 1 of this application maintains essentially unchanged transmittance and reflectance in the near-infrared range of 780nm-2500nm before and after heat treatment. Furthermore, Comparative Example 1 shows a greater increase in transmittance in the near-infrared region. This is attributed to the decrease in oxygen hole concentration in the film due to oxygen in the air penetrating into the film surface, or to a decrease in carrier concentration due to fluorine ion doping concentration in the film caused by high-temperature heat treatment. Therefore, it is demonstrated that the high-temperature resistant composite coated glass prepared in the embodiments of this application possesses stable optical properties at high temperatures.
[0075] (4) The high-temperature resistant composite coated glass prepared in Examples 1-2 of this application and the composite coated glass prepared in Comparative Example 1 were subjected to Hall effect tests before and after high-temperature heat treatment. The test results are shown in Table 1 below: Table 1
[0076] As shown in Table 1, the composite coated glasses prepared by the methods in Examples 1 and 2 of this application exhibit relatively small changes in resistivity, mobility, carrier concentration, and resistance before and after high-temperature heat treatment. The carrier concentration change rate in Example 1 is reduced to 1%. However, the transparent conductive oxide coated glass prepared in Comparative Example 1 shows significant changes in resistivity, mobility, carrier concentration, and resistance before and after high-temperature heating. The carrier concentration change rate in Example 1 is reduced by 6.9%. It is evident that the transparent conductive oxide coated glasses prepared in the embodiments of this application possess more stable conductivity at high temperatures. This indicates that the substrate temperature for the first chemical vapor deposition is higher than that for the second chemical vapor deposition, and the substrate temperature for the first chemical vapor deposition is above 660°C. This allows for the formation of a composite transparent conductive oxide layer with higher crystallinity, denser crystal particle packing, better continuity, and higher density, preventing significant changes at high temperatures and maintaining the stability of the microstructure. Furthermore, the mean free path of the free carriers at high temperatures is much smaller than the grain size, which reduces the influence of grain boundary scattering on the Hall mobility of the composite transparent conductive oxide layer. Therefore, the composite coated glass prepared in the embodiments of this application has more stable electrical conductivity at high temperatures.
[0077] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A method for preparing composite coated glass, characterized in that, Includes the following steps: Provide glass substrate; A shielding layer is prepared on the surface of the glass substrate; A first antireflective layer is prepared on the surface of the shielding layer opposite to the glass substrate; A second antireflection layer is prepared on the surface of the first antireflection layer that is opposite to the shielding layer; A first conductive layer is prepared on the surface of the second antireflection layer away from the first antireflection layer, including a first chemical vapor deposition using a first tin source, a dopant, a catalyst, and an oxidant as gaseous raw materials; A second conductive layer is prepared on the surface of the first conductive layer away from the second antireflection layer, including performing a second chemical vapor deposition using the first tin source, the dopant, the catalyst and the oxidant as gaseous raw materials to obtain a composite coated glass; Wherein, the substrate temperature of the first chemical vapor deposition is higher than that of the second chemical vapor deposition, and the substrate temperature of the first chemical vapor deposition is above 660°C, so as to form a high-temperature resistant composite transparent conductive oxide layer. The first conductive layer is a fluorine-doped tin dioxide layer; The second conductive layer is a fluorine-doped tin dioxide layer; The refractive index of the second conductive layer is less than that of the first conductive layer.
2. The preparation method according to claim 1, characterized in that, The substrate temperature for the first chemical vapor deposition is above 670°C; and / or, The substrate temperature for the second chemical vapor deposition is above 650°C.
3. The preparation method according to claim 1 or 2, characterized in that, The first tin source is selected from at least one of trichloromonobutyltin, dichlorodimethyltin, tetramethyltin, and tin tetrachloride; the dopant is selected from at least one of ammonium fluoride, trifluoroacetic acid, hydrofluoric acid, and tetrabutylammonium fluoride; the catalyst is selected from deionized water; and the oxidant is selected from oxygen; and / or, The molar ratio of the first tin source, the dopant, the catalyst and the oxidant is 1:(0.41~1.16):(3.16~5.82):(8.19~13.45).
4. The preparation method according to claim 1, characterized in that, The step of preparing a first antireflective layer on the surface of the shielding layer away from the glass substrate includes: using nitrogen and helium as carrier gases, and silane, ethylene, and oxygen in a molar ratio of 1:(5.3~6.7):(3.2~4.8) as gaseous raw materials, performing a third chemical vapor deposition on the surface of the shielding layer away from the glass substrate at a substrate temperature above 680°C to obtain the first antireflective layer; and / or, The step of preparing a second antireflection layer on the surface of the first antireflection layer away from the shielding layer includes: using nitrogen and helium as carrier gases, and silane, ethylene and oxygen in a molar ratio of 1:(5.3~6.7):(3.2~4.8) as gaseous raw materials, performing a fourth chemical vapor deposition on the surface of the first antireflection layer away from the glass substrate at a substrate temperature above 670°C to obtain the second antireflection layer.
5. The preparation method according to claim 4, characterized in that, The step of preparing a shielding layer on the surface of the glass substrate includes: Using nitrogen and helium as carrier gases, and isopropyl titanate and oxygen in a molar ratio of 1:(3.4~7.1) as gaseous raw materials, a fifth chemical vapor deposition is performed on the surface of the glass substrate at a temperature above 690°C to obtain a shielding layer; and / or, Using nitrogen and helium as carrier gases, and the first tin source, tetraethyl orthosilicate, triethyl phosphite, deionized water, and oxygen in a molar ratio of 1:(0.96~1.32):(0.48~0.72):(0.94~1.29):(19.67~22.09) as gaseous raw materials, a fifth chemical vapor deposition is performed on the surface of the glass substrate at a temperature above 690°C to obtain a shielding layer.
6. The preparation method according to claim 5, characterized in that, The shielding layer includes a tin dioxide layer, a titanium dioxide layer, and a SnSiO layer. x Any of the P-layers, wherein the refractive index of the shielding layer is 1.63~2.8, and the thickness of the shielding layer is 40nm~70nm; and / or, The first antireflection layer and the second antireflection layer are silicon dioxide layers. The refractive index of the first antireflection layer is 1.45~1.52, the refractive index of the second antireflection layer is 1.42~1.5, and the thickness of both the first antireflection layer and the second antireflection layer is 10nm~30nm.
7. The preparation method according to claim 3, characterized in that, The refractive index of the first conductive layer is 1.82~1.9, and the thickness of the first conductive layer is 150nm~400nm; and / or, The refractive index of the second conductive layer is 1.79~1.86, and the thickness of the second conductive layer is 200nm~400nm.
8. The preparation method according to claim 7, characterized in that, The transmittance of the composite coated glass is 81%~85%; and / or, The carrier concentration of the composite coated glass is 2.6 × 10⁻⁶. 20 ~4.2×10 20 / cm - ³; and / or, The resistance of the composite coated glass is 6~12Ω / □.
9. The preparation method according to claim 7, characterized in that, After the composite coated glass passes the high-temperature heat resistance test, the carrier concentration change rate of the composite coated glass is less than 5%. The high-temperature heat resistance test is set to be conducted on the composite coated glass at a temperature of 600-700℃ in an air atmosphere for at least 2.5 hours.
10. A solar cell, characterized in that, The composite coated glass is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-temperature-resistant transparent conductive oxide coated glass as well as preparation method and application thereof
CN117735857A
Low-emissivity coated glass with four-layer film structure
CN203344423U